The temporal and spatial variations of low frequency geomagnetic pulsations at polar cusp and cap latitudes - Kleimenova, N. G.; Francia, P.; Villante, U.; Kozyreva, O. V.; Bitterly, J.; Schott, J. J. (1999)
Geomagnetic field measurements at two Antarctic stations are compared during two weeks in the local summer (January 1-15, 1992). Low frequency (0.6-6 mHz) pulsations are observed at each station near local magnetic noon. The same wave packets appear in some cases also at the other station, although with a significant attenuation, more clearly in the morning sector; the waves show a near noon reversal of the polarization sense from counter-clockwise in the morning to clockwise in the afternoon indicating a westward and an eastward propagation, respectively. JCR Journal open